Analysis of the Effect of Customer Perceived Value, Service Quality, Patient Experience and Patient Trust on Patient Satisfaction as an Intervening Media and Its Impact on Outpatient Loyalty at Hospitals in Depok - Sugeng Sugeng; Hendra Achmadi (Syntax Corporation, 2023)
This Study aims to find out and analyze the effect of customer perceived value, service quality, patient experience, and patient trust on patient satisfaction and patient loyalty on public hospital in Depok, Indonesia. This Research is quantitative study where the data from 105 patients who had visited the hospital in Depok using an online questionnaire during the COVID-19 Pandemic. Factor analysis and Structural Equation Modeling (SEM) were analyzed using PLS-SEM of how customer service value, Service Quality, patient experience and patient trust impact to Patient satisfaction and patient loyalty. The result show that Service quality positively and significantly affect patient satisfaction (0.261) with t-statistics (2.431 > 1.96) or P value (0.015 < 0.05). Patient trust has a significant influence on patient satisfaction of (0.278) with t-statistics (2.287 > 1.96) or P value (0.022< 0.05). Patient trust has the highest influence on patient satisfaction of 0.278 compared to patient experience, service quality, and perceived value. The Patient satisfaction has a significant influence on patient loyalty (0.572) with t-statistics (7.780 > 1.96) or P value (0.000 < 0.05). The Implication of this study is that management of a public hospital needs to improve patient trust and Service Quality so that patient satisfaction can be improved which in turn can gain patient loyalty.